STUDY OF GAS SEPARATION PROCESS BY DYNAMIC ADSORPTION IN FIXED BED - Ioan Solomon; Maria Spiridon; Marius Sebastian Secula; Stelian Petrescu (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
An experimental study of mass transfer at gas separation by dynamic adsorption in fixed bed of impregnated silica gel is presented in this work. By means of a mathematical model based on constants and coefficient easy to evaluate, the distributions of adsorbate concentration in gas and solid phases were determined as a function of time and throughout the height of the fixed bed, under isothermal conditions.With this aim, water vapors from air were adsorbed in a fixed bed of impregnated silica gel. The values of the volumetric mass transfer coefficient, Kv, were determined experimentally at several values of air superficial velocity, an air relative humidity of 6920at 38 °C. The influence of the gas flow velocity and initial water concentration in adsorbent on the distribution of water concentration in both phases was established as a function of time and throughout the height of the fixed bed. The results obtained allow one to determination of the local adsorption rate.